The Effect of Awareness, Economic Conditions, E-Samsat Facilities, and Tax Sanctions on Motor Vehicle Taxpayer Compliance - Ni Nyoman Trisya Kusuma Putri; Putu Ery Setiawan (International Journal of Economics Development Research (IJEDR), 2024)
Taxes are mandatory contributions to the state owed by individuals or entities that are compelling according to law and are used for state purposes for the greatest prosperity of the people. The importance of tax revenue causes the government to continuously strive to increase the target of state revenue from the tax sector. This study aims to examine the effect of awareness, economic conditions, E-Samsat facilities, and tax sanctions on motor vehicle taxpayer compliance. The population in this study were motor vehicle taxpayers registered with the Badung Regency samsat office as of December 31, 2023, totaling 442,105 motor vehicle taxpayers. The sample was obtained using the slovin formula, namely 100 taxpayers, and using the accidental sampling method. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that taxpayer awareness, E-Samsat facilities, economic conditions, and tax sanctions have a positive effect on motor vehicle taxpayer compliance at the Badung Regency SAMSAT Office.